コウクウキ トウサイ ヒカリ サンランシキ ニ ヨル エアロゾル リュウシスウ コンゴウヒ ノ カンソク - 渡辺, 征春; ワタナベ, マサハル; 岩坂, 泰信; イワサカ, ヤスノブ; 長谷, 正博; ナガタニ, マサヒロ; 中田, 滉; ナカタ, ヒロシ; 山形, 定; ヤマガタ, サダム; 猪股, 弥生; イノマタ, ヤヨイ; et al. (2002)
P(論文) 98年3月に名古屋を起点として北極点を横断する北極航空機観測計画AAMP 98が実施された．ガルフストリームII型双発ジェット機の胴体下部に光散乱式粒子計数器（Optical Particle Counter, OPC）が搭載され，中緯度～極域の対流圏，成層圏エアロゾル粒子数混合比が計測された．観測結果は成層圏（高度12 km巡航）では水平方向には非常に粒子数の変化が少ない，安定した数濃度分布の状態を示したが，数カ所で粒子数に大きな変化が見られた．客観解析，および流跡線解析デー タと比較した結果，極ジェット外縁部，特に気圧の谷東側付近で発生している温暖コンベアーベルトの影響を受けた上昇気流が，この粒子数変化の原因である可能性が高いことが分かった． Particle number mixing ratios of tropospheric and stratosphenc aerosols were observed in the Arctic Airborne Measurement Program 1998 (AAMP 98) using an Optical Particle Counter onboard a sub-sonic aircraft, the Gulfstream II (G-11) in March 1998. The observational results showed horizontally homogeneous distributions of particle number mixing ratio at the cruise altitude (about 12 km). On the other hand, distinct size-number distributions were found at some points on the flight paths, which suggest that effects of the warm conveyor belts appeared eastward of trough of atmospheric pressure. The characteristics of observed particle size-number distributions are discussed with isentropic backward trajectory analyses and geopotential maps. departmental bulletin paper